Socialist Calculation II:: The State of the Debate - Hayek, Friedrich August von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
In this second article on the problem of socialist calculation, the author analyzes alternative socialist proposals which participated in the discussions on the subject. Particularly, the author presents and discusses the proposals to abolish private property and mantain the state ownership of the means of production, while preserving competition. It is concluded that preserving competition in a socialist framework necessarily leads to waste and meaningful losses in productivity.